2018
DOI: 10.1093/jme/tjy122
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Borrelia sp. From Ixodes granulatus Ticks Collected From Rodents in Malaysia

Abstract: The Borrelia genus consists of spirochete bacteria known to cause Lyme disease (LD) and relapsing fever in humans. Borrelia pathogens are commonly transmitted via arthropod vectors such as ticks, mites, or lice. Here, we report the molecular screening of LD group Borrelia sp. from ticks (Acari: Ixodidae) collected from rodents trapped in recreational forests and a semiurban residential area in the Selangor state in Malaysia. Of 156 adult ticks surveyed, 72 ticks were determined as positive for Borrelia sp. by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…In this study, we performed the molecular detection and phylogenetic analysis of B. burgdorferi s. l. in engorged ticks from wild rodents in nine regions of the ROK. Nested PCR revealed an overall Borrelia infection rate of 33.6% among the 738 ticks analyzed, similar to the high prevalence rates found in ticks feeding on wild rodents in Malaysia (46.1%) and Taiwan (47.1%) [23,24]. However, previous studies from the ROK have detected very low rates of B. burgdorferi s. l. in ticks feeding on wild animals such as dogs (0.2%, n = 562 ticks) [20], wild water deer (2.1%, n = 48 ticks) [19], migratory birds (3.7%, four positive pools of 108 tested pools among 212 ticks) [18], and wild rodents in northern Gyeonggi near the demilitarized zone (1.0%, n = 1,618 ticks including 933 questing ticks) [25].…”
Section: Discussionsupporting
confidence: 70%
“…In this study, we performed the molecular detection and phylogenetic analysis of B. burgdorferi s. l. in engorged ticks from wild rodents in nine regions of the ROK. Nested PCR revealed an overall Borrelia infection rate of 33.6% among the 738 ticks analyzed, similar to the high prevalence rates found in ticks feeding on wild rodents in Malaysia (46.1%) and Taiwan (47.1%) [23,24]. However, previous studies from the ROK have detected very low rates of B. burgdorferi s. l. in ticks feeding on wild animals such as dogs (0.2%, n = 562 ticks) [20], wild water deer (2.1%, n = 48 ticks) [19], migratory birds (3.7%, four positive pools of 108 tested pools among 212 ticks) [18], and wild rodents in northern Gyeonggi near the demilitarized zone (1.0%, n = 1,618 ticks including 933 questing ticks) [25].…”
Section: Discussionsupporting
confidence: 70%
“…Recently, a Borrelia sp. closely related to B. yangtzensis was detected in Peninsular Malaysia from I. granulatus collected from different rodent species [ 30 ]. Takhampunya et al [ 40 ] also identified B. yangtzensis from one rodent and two tick pools of Ixodes spp.…”
Section: Discussionmentioning
confidence: 99%
“…were conducted in Peninsular Malaysia, where Borrelia spp., belonging to the RFB group, were detected in the Haemaphysalis hystricis ticks collected from wild boar carcasses [ 29 ]. Additionally, Borrelia spp., closely related to B. yangtzensis (a member of Bbsl), were reported from Ixodes granulatus collected from rodents [ 30 ]. Moreover, antibodies against LD were detected from both the urban and indigenous people communities; this provided the serological evidence of borrelial infection in humans [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Lyme borreliosis is widespread in the northern hemisphere countries and is an epidemic [3,17,18]. Various genospecies of Bbsl have been detected in different tick species, animals, and humans in several East and Southeast Asian countries such as Japan [19], China [19], Taiwan [19], Thailand [20,21], and Malaysia [22,23].…”
Section: Introductionmentioning
confidence: 99%